Evidence of Phosphonium‐Carbenium Dication Formation in a Superacid: Precursor to Fluorinated Phosphine Oxides. (28th December 2018) - Castelli, Ugo; Lohier, Jean‐François; Drukenmüller, Ines; Mingot, Agnès; Bachman, Christian; Alayrac, Carole; Marrot, Jérôme; Stierstorfer, Karin; Kornath, Andreas; Gaumont, Annie‐Claude; Thibaudeau, Sébastien
Abstract: Unambiguously confirmed by low‐temperature in situ NMR experiments, X‐ray diffraction and vibrational spectroscopy, phosphonium‐carbenium superelectrophiles are shown to be generated in strong acidic conditions. Representing crucial intermediates, their exploitation allows for the synthesis of unprecedented fluorinated (cyclic) phosphine oxides.